LEGISLATIVE REGULATION OF FOREIGN INVESTMENT IN UKRAINE - Zhyzhko, K. V. (Science and Transport Progress, 2009)
In this article the basic regulatory documents controlling the foreign investments in Ukraine are considered and the recommendations for their improvement are proposed. Main disadvantages of present situation retarding the investing in Ukraine are analyzed.